Small and Medium Enterprises
DOI: 10.4018/978-1-4666-3886-0.ch050
|View full text |Cite
|
Sign up to set email alerts
|

Green Manufacturing Practices and Performance among SMEs

Abstract: Due to the rise in environmental awareness, green technologies and practices have become the conscientious imperative expected from all manufacturing industries. Consequently, environmental initiatives are becoming an essential part of the strategic planning in organizations, including the small and medium enterprises (SMEs). Thus, the objectives of this study were to determine the extent of implementation in green manufacturing practices among the SMEs as well as to examine the relationship between those prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
2
6
0
1
Order By: Relevance
“…the works by (Cooper, 2011), (Ammenberg, et al, 2003), and the previous mentioned studies ( (Ramayah, et al, 2013), (Pandaya, 2013), ( SMEs are enterprises run on short-term investment with small to middle budgets, and they are not willing, or even they cannot afford, to invest a huge budget to be ISO certified. In many cases, the SME's aim will be to run its business with the minimum expenses possible.…”
Section: Barriers Of Smes In Following Emsmentioning
confidence: 99%
See 1 more Smart Citation
“…the works by (Cooper, 2011), (Ammenberg, et al, 2003), and the previous mentioned studies ( (Ramayah, et al, 2013), (Pandaya, 2013), ( SMEs are enterprises run on short-term investment with small to middle budgets, and they are not willing, or even they cannot afford, to invest a huge budget to be ISO certified. In many cases, the SME's aim will be to run its business with the minimum expenses possible.…”
Section: Barriers Of Smes In Following Emsmentioning
confidence: 99%
“…Researchers, e.g. (Ramayah, et al, 2013), (Pandaya, 2013), (Nee, et al, 2010), and (Hillary, 2004) tried to study the barriers for SMEs to adopt an EMS. R. Hillary sheds a light on this issue in her paper "Environmental management systems and the smaller enterprise," which focused on SMEs adaption of the European Eco-Management and Audit Scheme (EMAS) or the ISO 14001 (Hillary, 2004).…”
Section: Barriers Of Smes In Following Emsmentioning
confidence: 99%
“…Besides, SMP can improve production processes leading to quality products that satisfy customers' expectations and help grow an enterprise's market share [40]. Ramayah et al [16] examined the impact of SMP in Malaysian SMEs and indicated that practices such as reducing solid waste have a positive effect on competitive performance. In their study of companies from varied sectors in Turkey, Sezen and Çankaya [41] inferred that green manufacturing applications positively impact operations performance through enhancing production efficiency and occupational safety, and minimising production cost.…”
Section: Competitive Capabilities and Smpmentioning
confidence: 99%
“…Fourth, prior research on the key factors and operational outcomes of SM in SMEs in Romania barely exists. According to Ramayah et al [16], it is vital to validate the link between implementing SMP and the corresponding performance benefits. Thus, we may assert that this study contributes to theory and practice of SM as well as SMEs research.…”
Section: Introductionmentioning
confidence: 99%
“…Berikutan itu, pelbagai pendekatan telah diketengahkan untuk menangani konflik di antara alam sekitar dan aktiviti pembuatan. Dalam konteks ini, kajian literatur menyarankan agar pendekatan berasaskan kepada konsep 'hijau' (green) atau mesra alam sekitar menjadi keutamaan syarikat pembuatan PKS (Ramayah et al 2013;Yacob et al 2013). Lee (2009) menegaskan pendekatan ini mampu meningkatkan prestasi hijau (green performance) syarikat, terutamanya dalam aspek operasi dan alam sekitar secara serentak agar dapat berdaya saing dalam persekitaran perniagaan yang kian mencabar.…”
unclassified